Ranking of Risk Management Factors Influencing SMEs Organizational Performance - Aris, Amir; Al Shamsi, Nasser Salem Nasser (International Journal of Sustainable Construction Engineering and Technology, 2022)
UAE Small and Medium-Sized Enterprises (SMEs) play a central role in socio-economic transformation, poverty reduction, job creation, and wealth creation. However, most SMEs faced unsustainable growth due to a lack of managing risk. Hence, this paper presents a study on the ranking of risk management practices that influence SMEs’ organizational performance in the UAE. The study has identified 11 factors, and these factors were classified into four groups: risk management process; operational risk management; risk assessment, risk control. These factors were used in the questionnaire development used in the survey to measure the respondentsâ€™ perceptions of these factors. The data collected from the questionnaire survey were analysed to rank these factors using mean and standard deviation values scored by the individual factor. In the risk management process group, it was found that the highest rank is the treat risk. The second group is operational risk management. The highest-ranked factor is the system, followed by the third group, which is Risk assessment with risk prioritization as the critical factor. The highest-ranking factor for the final group, risk control, is the risk management plan. These findings will help the SMEs community to handle risk either at the planning or the implementation stage of their activities to ensure the sustainability of the SMEs industry in UAE.